2012
DOI: 10.5334/jbr-btr.628
|View full text |Cite
|
Sign up to set email alerts
|

GI tract wall visualization and distension during abdominal and pelvic multidetector CT with a neutral barium sulphate suspension: comparison with positive barium sulphate suspension and with water

Abstract: Objective: When examining patients with contrast-enhanced multidetector-row CT, we determined if the stomach and small bowel were visualized and distended better with a neutral barium sulphate suspension than with positive barium sulphate suspension or water. Materials and methods: After obtaining approval from our institutional review board, 156 patients (women: 84; mean age: 54 yrs) with no history of gastrointestinal tract disease were randomized prospectively to receive orally either 900 ml of neutral (0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…Another interesting finding in our study is that the ileum was more distended than the jejunum for all positions. This observation is in contrast to those of previous studies [16,21].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Another interesting finding in our study is that the ileum was more distended than the jejunum for all positions. This observation is in contrast to those of previous studies [16,21].…”
Section: Discussioncontrasting
confidence: 99%
“…Megibow et al16 and Oliva et al [21] demonstrated relatively better luminal distension and wall visualization in the stomach, which was followed by the small bowel, and each bowel segment (Duodenum, jejunum and ileum) showed similar luminal distension and wall visualization. The discrepancy between those results and ours could be explained by the volume of oral contrast media ingested as well as the time between oral contrast ingestion and CT scanning.…”
Section: Discussionmentioning
confidence: 96%
“…This observation is in contrast to those of previous studies. 16,21 Megibow et al 16 and Oliva et al 21 demonstrated relatively better luminal distension and wall visualization in the stomach, which was followed by the small bowel, and each bowel segment (duodenum, jejunum and ileum) showed similar luminal distension and wall visualization. The discrepancy between those results and ours could be explained by the volume of oral contrast media ingested as well as the time between oral contrast ingestion and CT scanning.…”
Section: Discussionmentioning
confidence: 97%
“…Multimodal contrast agents based on perfluorooctyl bromide have been used for many years to help image the liver, spleen, and vasculature 13 , 24 . Barium sulfate is a common orally-taken contrast agent used for imaging of the gastrointestinal tract 25 . In some countries, xenon gas is used clinically as an alternative to iodinated media in cerebrovascular imaging 26 .…”
Section: Radiopacity and The Application In Cvd Imagingmentioning
confidence: 99%